Lignocellulosic biomass fractionation with deep eutectic solvents - Carvalho, Ana Malta (2019)
This work focused on studying the efficiency of two types of deep eutectic solvents (DES) on the fractionation of Eucalyptus globulus wood main components, namely cellulose, hemicellulose and lignin. The hydrogen bond donors (HBD) used for DES preparation were the dicarboxylic acids oxalic (OxA) and malic (MA), or the aliphatic diols ethanediol (Eth), butanediol (But) and hexanediol (Hex). Choline chloride (ChCl) was used as a hydrogen bond acceptor (HBA) in all studied DES. In order to evaluate the DES fractionation ability, certain operation parameters were studied, such as water content (25, 50 and 75 wt%), temperature (100 and 120 °C ) and DES molar ratio (1:1 and 1:3). For the acidic DES systems, ChCl:OxA revealed to be more efficient than ChCl:MA in biomass delignification at all tested conditions. In general, the fractionation of biomass components was favored by the addition of water up to 25 wt% into DES, while higher water contents decreased the efficacy of DES. The increase of both acid molar ratio in DES from 1:1 to 1:3 and temperature from 100 to 120 °C favored delignification, although a more pronounced effect was observed for the latter. In this sense, ChCl:OxA (1:1) at 120 °C was the most efficient system in biomass delignification, obtaining an insoluble cellulose-rich fraction (CrF) and a lignin-rich fraction (LrF) as separated solid streams with recovery yields of 62.4 wt% (from the initial biomass) and 69.8 wt% (from the initial lignin content), respectively. FTIR-ATR and solid-state NMR analysis further confirmed this cellulose enrichment compared to the original biomass, although residual lignin was also present. Additionally, the increase of temperature and DES molar ratio enhanced unwanted side reactions, such as esterification between separated components and organic acids from DES. Regarding hemicelluloses extraction, the addition of water and increased acid molar ratio favored xylose production in the liquid fraction, reaching a maximum yield of 71.7 mol% with ChCl:OxA (1:3) at 50 wt% water content. This condition also allowed for low furfural production (5.4 mol%) revealing its selectivity towards xylose production. In regard to diol-based DES, ChCl:Hex (1:1) revealed the best performance on biomass fractionation among examined diol-based DES. The addition of water up to 25 wt% content to ChCl:Hex (1:1) disclosed a positive effect allowing for 49.9 wt% and 82.4 wt% CrF and LrF yields, respectively, at 120 °C for 4 h of treatment. Further FTIR-ATR and solid-state NMR analysis showed an absence of lignin content in CrF, demonstrating the efficient biomass delignification provided by ChCl:Hex (1:1). Once again, the addition of water favored xylose production, whereas diol-based DES at 50 wt% water content produced xylose yields nearby 50 mol% at 120 °C for 4 h. This condition also allowed for low furfural production (9.7 mol%). Moreover, a kinetic study comparing the biomass fractionation performance of ChCl:Hex with Hex demonstrated a faster biomass delignification and higher furfural yield when ChCl was present. This may indicate a key role of ChCl on both delignification and furfural production.